Prevalence of anatomical/orthopedic disorders and effective factors in children aged 6–14 years - Çetin, Aymelek; Mete, Burak (Indian Journal of Child Health, 2018)
Background: Musculoskeletal disorders are common among children. Community- and school-based studies have revealed that the complaint of pain in childhood associated with musculoskeletal deformities is common. Objective: The present study aims to examine the prevalence of extremity, spinal and chest wall deformities and other disorders in children aged 6–14 years, and to determine the relationship between these disorders and nutrition, benefiting from sunlight, and familial factors. Method: The present cross-sectional study was conducted among 625 children aged 6–14 years attending elementary and secondary schools in rural, urban, and suburban areas. Children were evaluated for kyphosis, scoliosis, lordosis, chest wall disorders, and other disorders. Families were also asked about the factors that may be associated with these disorders. Chi-square test and binary logistic regression test were used for data analysis and p<0.05 was considered statistically significant. Results: Anatomical/orthopedic disorders were detected in 30% of the children. The most common anatomical disorders are genu varum and chest wall deformities. The most important risk factor for the development of anatomical/orthopedic disorders was family history. In addition, being male and living in the city center are important risk factors. After 2 years of age, yogurt and cheese consumption decrease the risk of genu varum. Conclusions: The important risk factor in the development of anatomical/orthopedic disorders is familial-genetic features. Gender and nutrition are effective factors as well.